Promoting science teachers’ competencies in Tanzania: The significance of competence-based assessment approaches - Kanyabwoya, Angelina; Bwagilo, Huruma Olofea; Mugaya, Samweli, Tumain (Journal of Education For Sustainable Innovation, 2025)
This study examined how competence-based assessment approaches can promote the development of science teachers’competencies in diploma teacher colleges in Tanzania. The study used a multiple case study research design. Qualitative methods such as interviews, focus group discussions, documentary reviews and observations were employed, and data from 66 respondents were analyzed using thematic analysis. The findings indicated that the majority of science tutors still employed a traditional assessment approach, with traditional paper-and-pen assessments remaining dominant and few competence-based assessments, such as projects and practical work, being incorporated into science lessons in diploma teacher colleges. The minimal use of competence-based assessment approaches was due to a lack of skills, limited administrative support, a lack of, or delay to, teaching and learning materials, heavy teaching workloads, large class, and inflexibility. The study recommends the use of competence-based assessment approaches, the provision of in-door training, and the timely purchase of teaching and learning materials.